Spatial-Temporal Evolution Characteristics of NDVI in Middle and Lower Reaches of Lancang River Basin - YUAN Zeshen; CHEN Chenchen; LI Bogen; WANG Yuchun (Renmin Zhujiang)
Vegetation coverage plays an important role in soil and water conservation,atmosphere regulation,and maintenance of ecosystem stability,which influences regional hydrological and water-sediment processes and has important implications for hydropower development in the basin.This paper analyzes the spatial and temporal evolution mechanisms of the normalized difference vegetation index (NDVI) in the study area from 1998 to 2018 using the Mann-Kendall model coupled with Sen's slope estimator,with the middle and lower reaches of the Lancang River Basin as the study area.The results reveal that ① the annual average NDVI in the study area from 1998 to 2018 is 0.81,and NDVI increases year by year from north to south on the whole;② NDVI in the study area shows an insignificant increasing trend from 1998 to 2018,with a growth rate of 5.8 × 10-3/a;③ the sudden spatial changes in NDVI all occur in degraded areas.Against the background of increasing global warming and the frequent occurrence of extreme weather in the past two decades,the results of this study provide a scientific basis for future biodiversity conservation and ecological and environmental protection in the Lancang River Basin.